INOVASI TEMPE KEDELAI HITAM BERBASIS PEMBERDAYAAN: PELATIHAN, DEMONSTRASI, DAN PENDAMPINGAN IBU PKK DI KEMUMU, KABUPATEN BENGKULU UTARA - Melani Anisa Fitri; Hesti Pujiwati; Selly Ratna Sari; Aldo Wibowo; Mariana Makdalena; Nadiah Afifah; Nofri Hari; Okta Rahmansyah (Universitas Mataram, 2026)
Black soybeans contain bioactive compounds such as anthocyanins and isoflavones that provide health benefits, making them a potential source of functional food. However, their utilization in local communities remains limited due to the lack of product innovation and processing strategies. This condition highlights the need for community empowerment initiatives that involve PKK women’s groups to enhance creativity in local food processing. Through collaboration between students and the community, the innovation of black soybean tempeh can serve as an alternative productive activity. This program aims to strengthen the capacity of PKK women in Kemumu Village to process and market black soybean tempeh through product innovation and branding strategies. The implementation applied a participatory approach through training, demonstrations, and mentoring in production, packaging, and product promotion. Students were actively involved as facilitators to transfer knowledge and skills to the community. The program showed significant improvements in participants’ understanding and skills in producing hygienic and nutritious black soybean tempeh. Participants were also able to create more attractive product variations that could be developed as local food alternatives. Improved packaging strategies and the use of digital media as promotional tools enhanced the product’s image and market appeal. This participatory approach strengthened the entrepreneurial spirit of PKK women and encouraged household-level food diversification. Collaboration between students and the community proved effective in fostering creativity and expanding community-based marketing networks. The innovation of black soybean tempeh contributes to the empowerment of PKK women and supports food security as well as sustainable family welfare.